Key Factors in Improving the Maturity of Information Technology Governance: A Case Study of State-owned Enterprise in Indonesia - Rokhman Fauzi; Rahmat Mulyana (International Journal of Innovation in Enterprise System, 2020)
The assessment of IT governance maturity is part of the assurance function. The assessment is carried out to ensure technology support in achieving business goals. In this context, companies should comply with regulations, as well as the need to continue to improve the quality of implementation of IT governance. The average value of PT X's IT governance maturity in Year 2 has increased from 3.21 to 3.26. There is an increase in the average score of 0.05 over one year. Success factors in implementing IT governance must be maintained and encouraged to continue the grow. This research was conducted to identify what organizational initiatives to increase the maturity and what the key factors are. Factors identification is done using evidence analysis method based on CSF references and attributes criteria. The results of the analysis obtained key factors that strengthen the maturity. The main factors are CSF2 providing IT infrastructure that supports the development and exchange of IT applications and services (21.72%), and CSF4 staff development to meet professional IT HR qualifications (17.39%). On the other hand, maturity attribute which gave the biggest contribution was ATR1 related to policies and procedures (34.6%), and ATR3 related to defining goals and actions (30.77%).